SSME architecture design in reserving parking problems in Malaysia - Yass, A.A.; Yasin, N.M.; Alam, G.M.; Zaidan, B.B.; Zaidan, A.A. (Academic Journals, 2010)
Parking industries are so vital that no one functions if these industries do not function efficiently. Though this industry is undergoing a revolution, applying new technologies such as Service Science Management and Engineering (SSME) to achieve better performance and customer satisfaction, in Malaysia this industry is lagging behind. Against this concern, this study was undertaken with the purpose to unfold and understand the need for a more efficient parking management system to be implemented. The focus of this research is on integrating important components of business, management and technologies, in order to provide quality services for customers and thereby improve the management of parking systems. In a nutshell, the primary goal of this study is to improve the car parking service systems and this is carried out through service innovation which is inherently multidisciplinary. It further examines the many benefits of advanced parking management systems. This study used a quantitative approach and a questionnaire survey was used. The evaluation findings derived through a second survey showed beyond doubt that the proposed system has excellent advantages over the existing manual system.